Consumption of rodenticides by humans - Kishore, PV; Palaian, S; Prabhu, M; Mishra, P (Journal of Institute of Medicine Nepal, 2008)
Case report: Poisoning is a common problem worldwide. Among the various poisonings, rat poison accounts for a significant number of cases. The common rat poisons are anticoagulant containing (superwarfarins) and phosphide containing. In case of superwarfin poisoning, the major symptom is increased prothrombin time and the management is directed towards coagulation. In case of phosphide containing, the symptoms are non-specific and the patient should be managed symptomatically. We present three case vignettes of rat poisoning cases treated at our hospital. Since rat poisoning is a common problem, the hospitals should also develop standard treatment guidelines regarding the management of rat poisoning. One should also make the differential diagnosis of the poisoning based on the type of rat poison prior to the management. Keywords: Superwarfarin, prothrombin, Rodenticide The full text of this paper is available at Journal of Institute of Medicine website